2016
DOI: 10.1155/2016/3205396
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Forecasting Model Based on Empirical Mode Decomposition and the Cuckoo Search Algorithm: A Case Study for Power Load

Abstract: Power load forecasting always plays a considerable role in the management of a power system, as accurate forecasting provides a guarantee for the daily operation of the power grid. It has been widely demonstrated in forecasting that hybrid forecasts can improve forecast performance compared with individual forecasts. In this paper, a hybrid forecasting approach, comprising Empirical Mode Decomposition, CSA (Cuckoo Search Algorithm), and WNN (Wavelet Neural Network), is proposed. This approach constructs a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The core idea of CS is inspired by the breeding parasitic characteristics of cuckoo and combined with the Lévy flights behavior. For establishing the mathematic model of CS algorithm, we mainly use three idealized assumptions: (i) every cuckoo can only lay one egg in a randomly chosen nest for one time; (ii) the best nests with better eggs will be retained to next generation; (iii) the number of host nests are invariant during the whole search process [28]. In CS algorithm, a nest is regarded as a candidate solution.…”
Section: The Standard Cs Algorithmmentioning
confidence: 99%
“…The core idea of CS is inspired by the breeding parasitic characteristics of cuckoo and combined with the Lévy flights behavior. For establishing the mathematic model of CS algorithm, we mainly use three idealized assumptions: (i) every cuckoo can only lay one egg in a randomly chosen nest for one time; (ii) the best nests with better eggs will be retained to next generation; (iii) the number of host nests are invariant during the whole search process [28]. In CS algorithm, a nest is regarded as a candidate solution.…”
Section: The Standard Cs Algorithmmentioning
confidence: 99%
“…Chang et al [6] proposed a combined prediction model optimized by particle swarm optimization algorithm, compared it with a single model, and verified its reliability in power load prediction. Jiani et al [7] designed a hybrid prediction model combining empirical mode decomposition, cuckoo search algorithm and wavelet neural network, carried out experiments on halfhour power load in New South Wales, Australia, and found that the prediction results were very similar to the actual results. Chitzaz et al [8] trained the self recursive wavelet neural network through Levenberg Marquardt (LM) learning algorithm and verified the effectiveness of the method through experiments.…”
Section: Introductionmentioning
confidence: 95%
“…Ma & Liu applied the kernel function method to the grey model, proposed a new timeseries forecasting model, and demonstrated that this method outperforms the traditional grey model in practical applications [32]. Heng et al proposed a hybrid prediction model that is based on empirical mode decomposition (EMD) and the cuckoo search algorithm, which is used to obtain more accurate results for power load forecasting [33]. Wang et al proposed another hybrid prediction method for wind speed prediction that uses the decomposition method, BPNN and the genetic algorithm (GA) [34].…”
Section: Introductionmentioning
confidence: 99%